Distinct preoperative clinical features predict four histopathological subtypes of high-grade serous carcinoma of the ovary, fallopian tube, and peritoneum - Ohsuga, Takuma (BMC Cancer, 2017)
BACKGROUND: The Cancer Genome Atlas Research Network reported that high-grade serous carcinoma (HGSC) can be classified based on gene expression profiles into four subtypes, termed “immunoreactive,” “differentiated,” “proliferative,” and “mesenchymal.” We previously established a novel histopathological classification of HGSC, corresponding to the gene expression subtypes: immune reactive (IR), papillo-glandular (PG), solid and proliferative (SP), and mesenchymal transition (MT). The purpose of this study is to identify distinct clinical findings among the four pathological subtypes of HGSC, as well as to predict pathological subtype based on preoperative images. METHODS: We retrospectively assessed 65 HGSC cases (IR: 17, PG: 7, SP: 14, MT: 27) and analyzed preoperative images. RESULTS: All IR cases originated from either the ovary or fallopian tube (P = 0.0269). Significantly more IR cases were diagnosed at earlier stages (P = 0.0013), and IR cases displayed lower levels of ascites (P = 0.0014), fewer peritoneal lesions (P = 0.0080), a sporadic pattern of peritoneal lesions (P = 0.0016), a lower incidence of omental cake (P = 0.0416), and fewer distant metastases (P = 0.0146) compared with the other subtypes. MT cases were more likely to be of peritoneal origin (P = 0.0202), presented at advanced stages with higher levels of ascites (P = 0.0008, 0.0052, respectively), and more frequently had a diffuse pattern of peritoneal lesions (P = 0.0059), omental cake (P = 0.0179), and distant metastasis (P = 0.0053). A decision tree analysis estimated the histopathological subtypes based on preoperative images, with a sensitivity of 67.3%. CONCLUSIONS: Pathological subtypes of HGSC have distinct clinical behaviors, and preoperative images enable better prediction of pathological subtype. These findings may lead to individualized treatment plans if the effect of treatment based on the HGSC subtype is elucidated. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-017-3573-1) contains supplementary material, which is available to authorized users.